Effect of autumn nitrogen fertilization on winter oilseed rape growth and yield parameters - Juraj Béreš; David Bečka; Jaroslav Tomášek; Jan Vašák (Plant, Soil and Environment, 2019)
Autumn fertilization of winter oilseed rape with nitrogen was monitored in exactly delimited small field experiment in the period of 2013/14-2015/16. The cultivar used was DK Exstorm, sowing amount: 50 seeds/m2 and fertilizer applied in autumn was Ureastabil - granulated urea with urease inhibitor (NBPT). The application period was at the end of October, doses 40 and 80 kg N/ha. Research results confirmed a statistically important effect of autumn fertilization on growth of the above-ground biomass and roots. Statistically important effect on seed yield was confirmed, too. The dose of 40 kg N/ha resulted in the highest seed yield, on average by 10.6% higher than reference (5.7-6.5 t/ha). On the other hand, the dose of 80 kg N/ha increased the seed yield only by 7.4% on average (5.4-6.3 t/ha).Fertilization effects on the oil content and one thousand seeds' weight were statistically insignificant. The results show that considering the given local and weather conditions and low mineral nitrogen content in the soil, the most suitable nitrogen dose for autumn fertilization is 40 kg N/ha. This dose follows the nitrate directive rules, supports oilseed rape strengthening before winter and intensifies it for better seed yield.